2020
DOI: 10.1111/cob.12396
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' political party affiliation and clinical management of obesity

Abstract: Summary Studies have documented that few patients with obesity receive evidence‐based care. One provider characteristic that may impact clinical obesity care, but that has been under studied to date, is political party affiliation. This study sought to evaluate how primary care physicians (PCPs) report managing patients with obesity and assess whether there are differences between Democratic and Republican PCPs. This was a secondary analysis of a cross‐sectional survey of 225 PCPs registered to vote as Democra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In line with earlier research, we find that physicians are unwilling to simply implement in mechanistic ways rules that conflict with their personal and professional preferences, and that partisan bias can lead to unwarranted variation in patient care. 23 , 31 From a patient welfare perspective, our findings have both upsides and downsides.…”
Section: Discussionmentioning
confidence: 86%
“…In line with earlier research, we find that physicians are unwilling to simply implement in mechanistic ways rules that conflict with their personal and professional preferences, and that partisan bias can lead to unwarranted variation in patient care. 23 , 31 From a patient welfare perspective, our findings have both upsides and downsides.…”
Section: Discussionmentioning
confidence: 86%
“…Turner et al [ 31 ] found, among a nationally representative sample of active health care providers, that (1) knowledge of physical activity and dietary guidelines was limited and (2) understanding of the appropriate initiation, intensity, and duration of pharmacotherapy was often inconsistent with evidence-based guidelines. Another study found that PCPs were least likely to say they would prescribe medication or refer a patient to counseling [ 32 ]. Regarding CDSS features, a systematic review by Groenhof et al [ 33 ] found that design and usability were important drivers behind the success, noting that information should be displayed all at once and at one glance.…”
Section: Discussionmentioning
confidence: 99%
“…Ample research has documented the seriousness of the high number of people living with overweight as a public health problem and examined differences in rates of people with obesity by characteristics such as self-reported gender, ethnicity and socio-economic status [1][2][3]. Evidence also shows an association between doctors' political affiliation and their approach to the management of those living with obesity [4]. However, little research has explored the relationship between rates of people with obesity and individual political affiliation.…”
Section: Introductionmentioning
confidence: 99%